Recommendations for a future global CO2-calculation standard for transport and logistics. (November 2021) - Wild, Peter
Highlights: An official, global CO2 emission standard for transport/logistics is unavailable. A case study of CarbonCare (emission calculator) provides valuable insights. The developed blueprint for a global emission standard was discussed with experts. The study aims a presenting a harmonized, global CO2 emission standard. Abstract: A true global CO2 emissions standard is still not available. EN16258 is currently the most internationally accepted standard for transport and logistics. Moreover, most emission standards have been developed by associations for a single mode of transport or for specific regions (e.g., North America). This research suggests recommendations for a global standard for all modes of transport based on EN16258 for freight/logistics transportation. First, the most relevant standards and methods are addressed and explained. Based on ISO IWA 16, they are then compared and combined into a single overview. A case study of the introduction of CarbonCare (emission calculator) and its global transport customers were taken into account to incorporate practical guidelines for a blueprint. Finally, the blueprint is discussed with experts from all modes of transport, culminating in recommendations not only for transport operation but also for harmonizing warehousing, cooling and transshipment - incorporating simplicity, accuracy, flexibility and feasibility.